Determination Of Tin In Lead-Base, Copper-Base And Iron-Base Alloys By Spectrophotometry And Graphite Furnace Atomic Absorption Spectrophotometry - Jais, Umi Sibyan (1987)
This method development study of tin determination in alloys is divided into three parts, namely visible spectrophotometry,flameless atomic absorption spectrophotometry ( FAAS ) and classical methods. Visible spectrophotometry was chosen as the main technique because atomic absorption spectrophotometry by the flame mode ( another popular method for tin ) was known to give a lot of problems . However, FAAS using graphite furnace was also studied in this project since this appraoch was claimed to give better sensitivity. The spectrophotometric method of determining tin in alloys using catechol violet and cetylpyridinium bromide is discussed in detail.